2009
DOI: 10.1016/j.ijid.2008.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of socio-demographic and clinical characteristics of orphans and non-orphans among HIV-positive children in Ibadan, Nigeria

Abstract: It appears that the extended family system is currently coping with the orphan situation. There is need for provision of social and economic support to caregivers of children orphaned by AIDS before the family system is overwhelmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 11 publications
5
16
2
1
Order By: Relevance
“…Regional estimates from Kenya and Nigeria found that between 36% and 50% of orphaned children under the age of 15 were HIVinfected. 29,30 The median age at orphanhood for HIV-infected children in Nigeria was 24.0 months, suggesting that a substantial portion of children were orphaned while they were still young enough to be breastfed. A number of studies have also observed higher rates of maternal mortality among HIV-infected women when compared with their HIV-uninfected counterparts, indicating that HIV-exposed infants are at higher risk of becoming maternal orphans than infants of HIV-uninfected women.…”
Section: Other Settings Of Concernmentioning
confidence: 99%
“…Regional estimates from Kenya and Nigeria found that between 36% and 50% of orphaned children under the age of 15 were HIVinfected. 29,30 The median age at orphanhood for HIV-infected children in Nigeria was 24.0 months, suggesting that a substantial portion of children were orphaned while they were still young enough to be breastfed. A number of studies have also observed higher rates of maternal mortality among HIV-infected women when compared with their HIV-uninfected counterparts, indicating that HIV-exposed infants are at higher risk of becoming maternal orphans than infants of HIV-uninfected women.…”
Section: Other Settings Of Concernmentioning
confidence: 99%
“…Prevalence of the same in a clinic-based study from Nigeria was 36.4%. 8 A study conducted at an ART centre in Mumbai found that 40% of the pediatric patients have lost one or both parents. 9 Various studies differ in the patterns of orphan distribution in the community with some showing a predominance of paternal orphans 9,10,11 while others that of maternal orphans.…”
Section: Discussionmentioning
confidence: 99%
“…9 Various studies differ in the patterns of orphan distribution in the community with some showing a predominance of paternal orphans 9,10,11 while others that of maternal orphans. 8 The non-orphans were all staying with their parents. Most of the orphans were being cared for by either the surviving parent or the grandparents or uncle and aunts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations